2013
DOI: 10.1186/2251-7235-7-37
|View full text |Cite
|
Sign up to set email alerts
|

Influence of argon gas flow on mechanical and electrical properties of sputtered titanium nitride thin films

Abstract: This study has been focused on the linear and nonlinear behavior and investigative in single-ring resonator. Optical fiber ring resonators have great interest due to different applications, especially in communication, secured communication, slow light, fast light and light storage in optical buffers. There are many proposed applications of optical ring resonators. Optical fiber ring resonators can be readily constructed from standard optical fiber components, which allow their properties to be studied in a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 26 publications
(3 reference statements)
2
18
0
Order By: Relevance
“…Meanwhile, at R = 75%, the XRD diffraction peak broadened, grain size decreased, which resulted in a decreased number of pores (or increased film density) in the structure of the composite layer. This phenomenon further led to increased hardness [43] and a subsequent increase in film brittleness. Therefore, when considering that acoustic signals are discontinuous discrete signals, the film-substrate binding force slightly declined when this signal was relatively weak.…”
Section: Results and Analysis Of The Film-substrate Binding Forcementioning
confidence: 99%
“…Meanwhile, at R = 75%, the XRD diffraction peak broadened, grain size decreased, which resulted in a decreased number of pores (or increased film density) in the structure of the composite layer. This phenomenon further led to increased hardness [43] and a subsequent increase in film brittleness. Therefore, when considering that acoustic signals are discontinuous discrete signals, the film-substrate binding force slightly declined when this signal was relatively weak.…”
Section: Results and Analysis Of The Film-substrate Binding Forcementioning
confidence: 99%
“…37) Therefore, considering that the thickness of the TiO 2 layer is less than 5 nm, the tunnel effect surely contributed to the specimen's conductivity. TiC particles (electrically conductive materials) exist between the oxide film and metal Ti or in the oxide film as its structure, but TiC's electrical resistivity is similar to that of metal Ti at approximately 50 μΩ•cm, 14,15) so they may not have caused the significant decrease in electrical resistance.…”
Section: Changes In the Surface Structures Due To Nitricmentioning
confidence: 99%
“…Their electrical resistivity is 25-52 μΩ•cm, almost equal to that of metal titanium. 14,15) Annealing cold-rolled titanium sheets in a vacuum atmosphere readily causes TiC to form on the sheet surfaces, 16) and annealing them in a nitrogen gas atmosphere readily causes TiN and Ti 2 N to do so. 17,18) It has been reported that as an effect of the formation of nitrides, the contact resistance becomes smaller than 10 mΩ•cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, small grain sizes consisting in the crystallographic lattice of the compound, leading to densification of the crystallographic arrangement and hence to obtain this high hardness values. In addition, the hardness of coatings can be affected by crystal lographic orientation, and stoichiometry [19]. Thus, the atainment of the best crystallization quality can be attributed to the highest level of hardness.…”
Section: Fig 3 Cross-section Images Of the Tialvn Coatings Produced mentioning
confidence: 99%